Cognitive and neuroanatomical assessment of alexia and agraphia in Japanese: implications for the European languages - Sakurai, Yasuhisa (Frontiers in Human Neuroscience, 2025)
The Japanese language has a unique writing system that consists of kanji (morphograms, derived from Chinese characters) and kana (phonograms, a simplified form of kanji representing syllables). A kanji character has two distinct ways of reading: on-reading (Chinese-style pronunciation) and kun-reading (native Japanese pronunciation). Some kanji words have irregular kun-reading called jukujikun. Furthermore, kana characters have two script forms: hiragana (cursive form) and katakana (square form), each of which is used for different purposes. Because of these features, Japanese individuals with alexia and agraphia show characteristic symptoms. Lesion-to-symptom analyses and functional imaging studies developed beginning in the 1970s have reported the following findings: (1) kanji–kana dissociation in alexia/agraphia: pure alexia for kanji or kana, lexical agraphia for kanji, and phonological agraphia for kana; (2) on-kun dissociation in alexia: predominant kun-reading and jukujikun reading impairment in semantic dementia and selective on-reading impairment in the extensive posterior middle temporal gyrus lesion; and (3) allographic agraphia between hiragana and katakana.